Emerging Role of Direct Oral Anticoagulants in the Management of Heparin-Induced Thrombocytopenia. (March 2018) - Tran, Phu Ngoc; Tran, Minh-Ha
Heparin-induced thrombocytopenia (HIT) and heparin-induced thrombocytopenia with thrombosis (HITT) are rare but potentially limb- and life-threatening complications of heparin therapy. Continuation of heparin or low-molecular-weight heparin is contraindicated due to platelet activation in the presence of (heparin-dependent) HIT antibodies. Primary treatment options currently include argatroban, fondaparinux, or bivalirudin. However, the parenteral administration routes and interference of argatroban with traditional coagulation markers complicate management. The goal of this review is to assess the viability of direct oral anticoagulants as an alternative treatment option in patients with HIT/HITT. Their use in HIT/HITT is reasonable, given absent cross-reactivity preformed with HIT antibodies. Furthermore, their rapid onset of action and induction of effective anticoagulation provide a favorable basis for their use in this condition. Herein, we summarize 3 studies and 8 case reports comprising 56 patients in whom direct oral anticoagulants were used in the treatment of HIT/HITT.